Trading Commodities and Financial Futures: A Step-by-Step Guide to Mastering the Markets, Third Edition - Kleinman, George (Pearson, 2004)
More fortunes are made and lost more quickly in the commodity futures markets than anywhere else. It is a game of consequence where profits won by one player are lost by another. The stakes are high, but for those who know how to play well, the rewards can be immense. Trading Commodities and Financial Futures shows you how to play the game to win. In this book, one of the world's most experienced traders introduces a new step-by-step methodology built on more than twenty-five years of success. George Kleinman begins with the basics-including a complete primer on how futures and options trading works, how traders' psychology impacts the markets, and how to avoid the pitfalls that trip up so many traders. This edition offers updated coverage of electronic trading, the latest contracts, and state-of-the-art trading techniques you won't find in any competing book. Previous editions of Kleinman's Commodity Futures and Options became international best sellers. This one offers even more insight for winning the commodities game-and winning big. Winning in a zero-sum game For every commodities winner, there's a loser: here's how to be the winner The trend is your friend How to use techniques designed to generate profits in a trending market The fundamentals: supply and demand in every key market Mastering the markets, from crude oil to soybeans, gold to coffee, foreign exchange to stock index futures TMVTT: The most valuable technical tool A unique trading methodology-how it works and how to use it When to get in, when to get out How to recognize the beginning-and end -of major market moves Twenty-five trading secrets of the pros A lifetime's experience, distilled into twenty-five crucial tips.